Materials of the Third Conference “The Constitution of Russia Yesterday, Today, Tomorrow” (St. Petersburg, December 9–10, 2019), second part - article editotial (Теоретическая и прикладная юриспруденция)
This material is devoted to a review of expert speeches at the Conference “The Constitution of Russia: Yesterday, Today, Tomorrow”, held in St. Petersburg on December 9–10, 2019. The problems of modern federalism were discussed at the conference. The experts analyzed the origins and causes of the existing state structure in the Russian Federation, its features and possible development paths; possible ways of developing the state system of the Russian Federation in the direction of federalism, confederation and unitary state; discussed current issues and features of federalism.